A theoretical investigation on the sequence selective binding of adriamycin to double-stranded polynucleotides. - Chen, K S (1986)
Theoretical computations are performed on the structural and energetical factors involved in the sequence selective binding of adriamycin (ADM) to five self-complementary double-stranded hexanucleotides. Among the two regularly alternating hexanucleotides d (TATATA)2 and d (CGCGCG)2, a stronger binding is predicted for the former. The strongest complex is computed, however, for the mixed hexanucleotide d (CGTACG)2, containing the intercalation site between two CG base pairs and an adjacent TA base pair. The overall sequence preference is the result of an intricate interplay of sequence preferences of the constituents in particular of daunosamine and the 9-OH substituent. Altogether, the selective base pair recognition by adriamycin cannot be defined in terms of the two base pairs implicated in the intercalation site alone but must be expressed in terms of a triplet of base pairs.